Specific situations related to acute schistosomiasis in Pernambuco, Brazil - Constança Simões Barbosa; Silvia Maria Lucena Montenegro; Frederico Guilherme Coutinho Abath; Ana Lúcia Coutinho Domingues (Memorias do Instituto Oswaldo Cruz, 2001)
The present work reports on two epidemiological episodes resulting in acute schistosomiasis involving wealthy persons living in the State of Pernambuco, Brazil. The authors discuss the epidemiological, clinical and serologic characteristics of the acute infections and also the way in which the conditions for transmission occurred.